Hristologia biblică și cea a lui Ellen G. White în interpretarea lui M. L. Andreasen - Zoltán Szallós-Farkas (TheoRhēma, 2017)
The article addresses the issue of both biblical and Ellen G. White’s Christology being interpreted by M. L. Andreasen in a certain idiosyncratic manner. This led to the emergence of ethical perfectionism in some circles of the rank and file of Seventh-day Adventists (SDA). In an attempt to explain the delay of Christ’s parousia, Andreasen has taken upon himself the task to explain the delay by elaborating on the incarnate/human nature of Christ’s being identical, in terms of sinful propensities, to our fallen human nature. Identity then has been taken as the major presupposition for an understanding of the doctrine of atonement in which Christ had first to gain victory over his own fallen human nature, thus to be able to atone for fallen humanity. Issuing from such an understanding of Christology and soteriology there was the idea of the last generation believer’s need and potency to replicate Christ’s absolute victory over fallenness, thus attaining perfect sinlessness, which is the essence of moral perfectionism.